Answer:
-12
Explanation:
Let the number be A
Given if you divide the sum of six and the number A by 3 , the result is 4 more than 1/4 of A
That’s
6+A/3 = 4+1/4 of A
6+A/3 = 4+1/4 x A
6+A/3 = 4+A/4
Cross multiply
4(6 + A) = 3(4 + A)
Distribute
4 x 6 + 4 x A = 3 x 4 + 3 x A
24 + 4A = 12 + 3A
Subtract 24 from both sides to eliminate 24 on the left side
24 - 24 + 4A = 12 - 24 + 3A
4A = -12 + 3A
Subtract 3A from both sides so the unknown can be on one side
4A - 3A = -12 + 3A - 3A
A = -12
Check
6+(-12)/3 = 4 +(-12)/4
6 -12/3 = 4 -12/4
-6/3 = -8/4
-2 = -2